From ideological colonialism to national consciousness: national awakening efforts in the Kazakh press in the 20th century (Journal of Philosophy Culture and Political Science, 2024)
The media has a crucial role in shaping political, economic, and diplomatic relations, as well as raising national consciousness. In the early 19th century, the Kazakh press played a vital role in awakening the national consciousness of society against ideological colonialism. Propaganda, whether in favor or against, can be effectively conveyed through poetry, stories, epics, and newspapers. These messages, even when subtly delivered, have a strong impact on people and the public conscience of society.Whether in favor or against, propaganda through poetry, stories and epics, as well as through newspapers, is very important. The messages with hidden power, have a very strong effect on people and the public conscience of the society.The future of a country is a continuation of its past, and recognizing and accepting the past can enhance people's consciousness. Periodicals are an important aspect of Kazakh journalism worth studying. Many publications in the development of national journalism were enlightening, national-oriented, and promoted the spiritual wealth of Kazakh people, earning the country's respect. Periodicals that focused on the future of the nation created the preconditions for the Kazakh society's awakening in the early 20th century, leading to the national liberation movement.Key words: nation, Alash, press, periodicals, journalism, Kazakh, national movement, Periodicals.